Cover Picture: Live‐Cell‐Templated Dynamic Combinatorial Chemistry (Angew. Chem. Int. Ed. 39/2020). Issue 39 (4th August 2020) - Carbajo, Daniel; Pérez, Yolanda; Bujons, Jordi; Alfonso, Ignacio
Abstract : Dynamic covalent chemistry can be performed on the surface of living cells. In their Communication on page 17202, I. Alfonso et al. describe a live‐cell‐templated dynamic combinatorial chemistry approach for the identification of a strong binder to the glycosaminoglycans of the extracellular matrix of human lung adenocarcinoma cells. Cover image: M. Eugenio Vázquez, @ChemBioUSC.